PROFITABILITAS, RISIKO KEUANGAN DAN NILAI PERUSAHAAN, DAN PRAKTIK PERATAAN LABA - Lutfitasari, Feby; Lutfillah, Novrida Qudsi (EQUITY, 2018)
The research purpose is to test the partial and simultaneous effect of the variabel of profitability, financial risk, and firm value to the income smoothing practices. This research is done by quantitative approach upon the companies registered in BEI for 2013-2015 periods. The results showed that there was no significant influence partially and simultaneously variableprofitability, financial risk and corporate value to the practice of income smoothing.